2018
DOI: 10.1016/j.ihj.2017.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of contrast induced nephropathy and the applicability of the Mehran risk score in high risk patients undergoing coronary angioplasty—A study from a tertiary care center in South India

Abstract: The incidence of CIN in high risk patients undergoing PCI is substantially higher in our population compared to similar studies in the west. The MRS risk prediction is pertinent even in an Indian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
0
19
1
Order By: Relevance
“…[19][20][21][22][23][24][25][26][27][28] Recent studies have demonstrated the external validity of the Mehran score in populations from Spain, Japan, India, and those undergoing computed tomography imaging or transcatheter aortic valve implantation. [29][30][31][32][33][34][35] Furthermore, the Mehran score was validated to predict CIN in the setting of non-urgent PCI as well as primary PCI in patients with acute myocardial infarction. 34,36 However, the inclusion of contrast volume, which cannot be obtained until after the procedure, limits the utility of this score as a predictor of AKI before the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28] Recent studies have demonstrated the external validity of the Mehran score in populations from Spain, Japan, India, and those undergoing computed tomography imaging or transcatheter aortic valve implantation. [29][30][31][32][33][34][35] Furthermore, the Mehran score was validated to predict CIN in the setting of non-urgent PCI as well as primary PCI in patients with acute myocardial infarction. 34,36 However, the inclusion of contrast volume, which cannot be obtained until after the procedure, limits the utility of this score as a predictor of AKI before the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Hemoglobin levels and GFR were found to be predictors of CIN in patients treated with emergency PCI. 28,29 Mendi et al determined that there was a relationship between serum uric acid levels and CIN in patients with ST-segment elevation myocardial infarction (STEMI) who underwent primary PCI. 30 The association of new risk factor profile, which includes white blood cell count, body surface area, history of stroke, baseline SCr, intra-aortic balloon pump, and diuretics usage, with CIN in patients treated with emergency PCI was also reported.…”
Section: Discussionmentioning
confidence: 99%
“…They included PCI patients with normal renal parameters and excluded patients with risk of CIN such as known chronic kidney disease (stage 5), baseline creatinine >1.5 mg/dl, significant hypotension, anaemia and patients with myocardial infarction. Another study by Valappil et al [6] from Trivandrum, Kerala found a CIN incidence of 29 % where they included only patients with impaired renal function (GFR of 30-60 ml/min/ 1.73 m 2 ) and excluded patients with ST elevated myocardial infarction and cardiogenic shock as well as patients undergoing haemodialysis or peritoneal dialysis. These inconsistencies of inclusion and exclusion criteria may be a reason for the variability in incidence of CIN as both the studies used the same definition of CIN as ours.…”
Section: Resultsmentioning
confidence: 99%
“…Reported incidence of CIN varies (<2 to 30 %) depending up on the study population, the prevalence of associated risk factors and the definition of CIN [3,[6][7][8] . Patients undergoing coronary angiography or PCI have the highest CIN incidence compared to other procedures using contrast media for diagnostic or therapeutic purposes.…”
mentioning
confidence: 99%